2019
DOI: 10.1097/mcg.0000000000001135
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Hyperpermeability in Gulf War Veterans With Chronic Gastrointestinal Symptoms

Abstract: Background: Well over 700,000 United States military personnel participated in the Persian Gulf War in which they developed chronic health disorders of undetermined etiology. Up to 25% of Veterans had persistent and chronic gastrointestinal (GI) symptoms, which they suspected were related to their military service in the Gulf. Aim: The overall aim of the current study was to evaluate intestinal permeability in previously deployed Gulf War Veterans who d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…In a recent study incorporating all service branches, IBS was found to afflict close to 20% of Gulf War Veterans ( 6 ). Furthermore, GWI Veterans with chronic GI symptoms were found to exhibit intestinal epithelial hyperpermeability ( 7 ), which is consistent with IBS.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…In a recent study incorporating all service branches, IBS was found to afflict close to 20% of Gulf War Veterans ( 6 ). Furthermore, GWI Veterans with chronic GI symptoms were found to exhibit intestinal epithelial hyperpermeability ( 7 ), which is consistent with IBS.…”
Section: Introductionmentioning
confidence: 70%
“…Antimicrobial peptide (AMP) secretion by intestinal epithelial cells (IEC) is critical for regulating microbial colonization as dysregulation can lead to dysbiosis ( 15 ) and contribute to inflammatory bowel disease and IBS ( 16 ). Altered intestinal permeability has also been extensively linked to IBS, especially for post-infectious IBS ( 8 ) and for GWI Veterans ( 7 ). The formation of tight junctions between IECs in the gut barrier plays a significant role in regulating intestinal permeability ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…29,31 This condition of compromised gut barrier integrity has also been reported among veterans who suffer from gastrointestinal problems in GWI. 55 Moreover, a recent study by Janulewicz et al 56 showed that GWI afflicted veterans with gastrointestinal disturbances present gut dysbiosis among bacteria of the phylum Verrucomicrobia. Interestingly, A muciniphila belongs to the same phylum.…”
Section: Discussionmentioning
confidence: 99%
“…Among GW veterans, the study by Zhang et al [8] reports intestinal hyperpermeability in veterans who report GI symptoms. The study worked with veterans from The Cincinnati Veterans Affairs Medical Center (VAMC) in Cincinnati, OH and the Malcom Randall VAMC in Gainesville, FL.…”
Section: A Leaky Gut As a Portal For Immunostimulatory Particlesmentioning
confidence: 99%